Defective mitochondrial cardiolipin remodeling dampens HIF-1α expression in hypoxia - Chowdhury, Arpita; Wozny, Katharina; Lüchtenborg, Christian; Brügger, Britta (Cell reports, 2018)
Summary - Mitochondria fulfill vital metabolic functions and act as crucial cellular signaling hubs, integrating their metabolic status into the cellular context. Here, we show that defective cardiolipin remodeling, upon loss of the cardiolipin acyl transferase tafazzin, decreases HIF-1α signaling in hypoxia. Tafazzin deficiency does not affect posttranslational HIF-1α regulation but rather HIF-1α gene expression, a dysfunction recapitulated in iPSC-derived cardiomyocytes from Barth syndrome patients with tafazzin deficiency. RNA-seq analyses confirmed drastically altered signaling in tafazzin mutant cells. In hypoxia, tafazzin-deficient cells display reduced production of reactive oxygen species (ROS) perturbing NF-κB activation and concomitantly HIF-1α gene expression. Tafazzin-deficient mice hearts display reduced HIF-1α levels and undergo maladaptive hypertrophy with heart failure in response to pressure overload challenge. We conclude that defective mitochondrial cardiolipin remodeling dampens HIF-1α signaling due to a lack of NF-κB activation through reduced mitochondrial ROS production, decreasing HIF-1α transcription.
Gesehen am 07.05.2019